Democracy under stress The global crisis and beyond - Wnuk-Lipinski, Edmund; van Beek, Ursula J. (Verlag Barbara Budrich, 2011)
This book focuses on the global financial crisis of 2008-2009 and its implications for democracy. Why and how did the crisis come about? Are there any instructive lessons to be drawn from comparisons with the Great Depression of the 1930s? What are the democratic response mechanisms to cope with serious crises? Do they work? Is China a new trend setter? Do values matter? Are global democratic rules a possibility? These are some of the key questions addressed in the volume.
Description based on print version record.
KU Select 2018: HSS Backlist Books
Keywords: Political Science / Comparative Politics; Political science; Electronic books